Distribusi Nitrogen pada Budidaya Ikan Koi (Cyprinus Rubrosfuscus) dalam Sistem Vertiqua Menggunakan Biofikal Filter Atas - Indra Maulana Fattah; Ujang Dindin; Novita Mz (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
Vertiqua is an innovation in vertical cultivation on limited land and water. Vertiqua continues to be developed to be effective in cultivating fish. This research aims to examine the effectiveness of nitrogen distribution in vertiqua using biofical top filters. The analysis used is quantitative analysis by calculating and testing the data that has been collected. Total nitrogen feed input, total nitrogen wasted, and percentage of nitrogen absorption were calculated using existing formulas. Comparative testing using the T – test on the Mini Tab application was carried out to test the effectiveness of nitrogen absorption. The research results showed that nitrogen absorption in the vertiqua using the top biofical filter was effective, ranging from 198,12 – 200,89 mg/l. Nitrogen absorption in the vertiqua without using a biofical top filter ranges from 42,75 – 43,35 mg/l. The distribution value of effective nitrogen absorption in vertiqua using the top biofical filter is shown by a P value <0,05. Vertiqua with a biofical top filter is also able to reduce nitrogen levels so that fish survival is good.